Violence‐Related Trauma from the Cistercian Abbey of St Mary Graces and a Late Black Death Cemetery. (12th June 2015) - Krakowka, K.
Abstract: The skeletal assemblage excavated from the precinct of St Mary Graces in London (part of the MIN86 collection curated at the Museum of London) is composed of two separate burial populations: the abbey burials, both intra‐ and extramural, and the western cemetery, which was a burial ground for victims of the later waves of the Black Death. Representing both ends of the social status spectrum, these two cemeteries offer a unique look at the patterns and prevalence of violence in a small cross section of the medieval London population. The lower status males from the western cemetery presented with a large number of skull fractures, indicating a high level of violence. The high‐status individuals buried within the abbey were not immune from violence‐related trauma. They presented with a large number of rib fractures, possibly a result of combat or combat practice as many of these individuals were knights and lords. Copyright © 2015 John Wiley & Sons, Ltd.